2019
DOI: 10.1002/lno.11200
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic inputs from a coastal megacity are linked to greenhouse gas concentrations in the surrounding estuary

Abstract: Coastal megacities deposit significant amounts of carbon (C), nitrogen (N), and pollutants into surrounding waters. In urbanized estuaries, these inputs, including wastewater discharge and surface runoff, can affect biogeochemical cycles, microbial production, and greenhouse gas (GHG) efflux. To better understand estuarine GHG production and its connection to anthropogenic drivers, we quantified carbon dioxide (CO2) and methane (CH4) surface‐water concentrations and efflux in combination with a suite of biogeo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 88 publications
(113 reference statements)
1
14
0
Order By: Relevance
“…Inner and low-salinity estuarine regions have been documented as heterotrophic and large CO2 emitters (Frankignoulle et al 1998;Silvennoinen et al 2008). In several coastal waters worldwide, important CO2 changes have been strongly related to eutrophication (Borges and Gypens 2010;Cai et al 2011;Sunda and Cai 2012;Cotovicz et al 2015;Brigham et al 2019). Overall, when untreated urban wastewater discharges from megacities reach estuarine waters, they enhance the levels of CO2 especially in turbidity coastal waters located at the vicinity of outfalls (Frankignoulle et al 1998;Zhai et al 2007;Sarma et al 2012;Brigham et al 2019).…”
Section: 3spatial Distributions Of Dissolved Co2 and Ch4 In The Jlcmentioning
confidence: 99%
See 2 more Smart Citations
“…Inner and low-salinity estuarine regions have been documented as heterotrophic and large CO2 emitters (Frankignoulle et al 1998;Silvennoinen et al 2008). In several coastal waters worldwide, important CO2 changes have been strongly related to eutrophication (Borges and Gypens 2010;Cai et al 2011;Sunda and Cai 2012;Cotovicz et al 2015;Brigham et al 2019). Overall, when untreated urban wastewater discharges from megacities reach estuarine waters, they enhance the levels of CO2 especially in turbidity coastal waters located at the vicinity of outfalls (Frankignoulle et al 1998;Zhai et al 2007;Sarma et al 2012;Brigham et al 2019).…”
Section: 3spatial Distributions Of Dissolved Co2 and Ch4 In The Jlcmentioning
confidence: 99%
“…For CH4, the eutrophication is related to increasing concentrations in aquatic compartments. Pristine rivers are usually organic matter poor-environments and weak sources of CH4 compared to impacted ecosystems (Richey et al 1988;Purvaja and Ramesh 2000;Brigham et al 2019). The production of CH4 increases with hypoxic and anoxic conditions associated to the increased inputs of organic matter to water and sediments.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In other urbanised catchments, the presence of elevated concentrations of DOC coupled with an absence of thermodynamically favourable electron acceptors has been shown to facilitate the proliferation of methanogenic archaea [ 14 , 65 , 66 ]. This implies that increased inputs of organic matter due to catchment urbanisation and modification may lead to an increase in methanogenesis and GHG production [ 11 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estuaries contribute between 1 and 7 Tg of CH 4 and 0.1 to 0.25 Gt of CO 2 to the atmosphere each year [9], with the global flux of CO 2 to the atmosphere from estuaries comparable to the uptake of the entire continental shelf, despite estuaries representing only 5% of the continental shelf equivalent surface area [10]. Increasing inputs of anthropogenic pollutants stemming from urban, industrial and agricultural runoff into adjacent estuarine ecosystems have been reported to elevate GHG fluxes [11][12][13]. CH 4 emissions originating from microbial sources have been suggested to contribute about 70% of all global methane emissions [14][15][16].…”
Section: Introductionmentioning
confidence: 99%